Обалденная вечеринка! Игры и розыгрыши для взрослых и не очень - Велижанина Д. (Зажигаем!, 2010)
Экземпляры: ф.1 (09.03.2011) / Инвентарный номер: 45921 / Цена: 196-65 / Авт.знак: В 27 / ГРНТИ: 18.46 / ББК: 74.200.58